PEMBUATAN UREA PELEPASAN LEPAS LAMBAT MELALUI PELAPISAN DENGAN AMILUM-ACRYLIC - Margie Agami Haq; Septiana Triwiningsih; S Suherman (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
The controlled release technology by coating for increasing the efficiency of fertilizer can reduce fertilizer’s losses and minimize environmental pollution. Starch mixed with acrylic acid, PEG and water were used as coating solution. The coating process of granular urea was conducted in fluid bed spray coater. The influence of bed temperature, and concentration of starch on properties of coated urea product was investigated. Microscopic analysis by SEM shows the formation of a thin layer on the surface of coated urea product that has a different morphology, more compact, and any irregularities of the crystal. The dissolution rate of the product decraesed with increasing concentration of starch and decreasing bed temperature. The percent coating of the product increased with increasing concentration of starch and decreasing bed temperature. The dustiness of the product increased with increasing starch concentration and bed temperature.